Dimensional model of adolescent personality pathology, reflective functioning, and emotional maltreatment - Ensink, Karin; Deschênes, Mélissa; Bégin, Michaël; Cimon, Laurie; Gosselin, Thomas; Wais, Marissa; Normandin, Lina; Fonagy, Peter (Frontiers in Psychiatry, 2024)
Childhood emotional abuse (CEA) is a recognized risk factor for adolescent mentalizing challenges. However, there's limited understanding about how CEA might influence personality development and elevate the risk of adolescent personality pathology. A deeper grasp of these pathways is crucial, given that adolescence is a pivotal developmental phase for identity integration, personality consolidation, and the emergence of personality disorders. As the emphasis shifts to dimensional perspectives on adolescent personality pathology, the spotlight is increasingly on adolescents' evolving personality organization (PO). Within this framework, personality disorder manifestations stem from inherent vulnerabilities in PO. A comprehensive understanding of how CEA leads to these inherent vulnerabilities in PO can inform enhanced interventions for at-risk adolescents. Nonetheless, our comprehension lacks insight into potential pathways to PO, especially those involving external factors like maltreatment and individual traits like mentalizing. This study sought to bridge these gaps by employing latent factor analysis and structural equation modeling to explore connections between emotional maltreatment, adolescent mentalizing, and PO. A community-based cohort of 193 adolescents (aged 12-17) took part in self-report assessments: the Childhood Experience of Care and Abuse Questionnaire (CECA.Q), the Reflective Functioning Questionnaire for Youth (RFQ-Y), and the Inventory for Personality Organization for Adolescents (IPO-A). The structural equation model revealed a significant direct influence of CEA on both RFQ-Confusion and PO, and a noteworthy direct effect of RFQ-Confusion on PO. Remarkably, the model accounted for 76.9% of the PO variance. CEA exhibited a significant indirect impact on PO through RFQ-Confusion, which was accountable for 52.3% of the CEA effect on PO, signifying a partial mediation by mentalizing. These insights carry substantial clinical implications, especially for This is a provisional file, not the final typeset article devising integrated, trauma-informed strategies for adolescents with personality pathologies. This is particularly relevant for enhancing mentalizing and bolstering personality consolidation among adolescent CEA survivors.